Business Plan : Creative Coworking Workshop in Belgrade - Aslamov, Bogdan; Pernica, Karel; Kubíček, Aleš; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This bachelor thesis presents a comprehensive business plan for Work@Create, a creative coworking space in Belgrade, Serbia, designed to meet the evolving needs of freelancers, remote professionals, and creative entrepreneurs. The project responds to the growing demand for multifunctional, community-driven, and inclusive work environments that go beyond traditional office offerings. Grounded in a combination of theoretical frameworks and practical tools including SWOT, PESTEL, Porter’s Five Forces, Business Model Canvas, and TAM/SAM/SOM analysis the thesis investigates the feasibility and strategic viability of entering the coworking market in Serbia. The practical part outlines the operational, financial, and marketing strategies of Work@Create, highlighting key differentiators such as flexible membership plans, workshops, a Showroom Corner, and inclusive services for marginalized groups. Financial projections estimate a break-even point within the first 10 months and a growing net profit reaching nearly €100,000 by year four. The study concludes that Work@Create is not only economically feasible but also strategically positioned to contribute to Serbia’s creative economy and social inclusion through innovation, community-building, and professional development.
Vedoucí práce: Karel Pernica
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses